Problems of Reliance on Lexicons in Linguistic Criticism: A Diachronic Study - Murtadha Hamdan Ajib ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
This research addresses the issue of relying on linguistic dictionaries in the corrections made by both classical and modern critics. By critics, we mean all those who have practiced linguistic criticism, whether in dedicated works or through occasional critiques within their linguistic writings. The Arabic linguistic dictionary has been a fundamental pillar in combating grammatical errors and preserving the Arabic language since its earliest beginnings, culminating in comprehensive lexicographical encyclopedias. It has thus held a prominent position among critics, both past and present.Due to the errors and distortions that linguistic dictionaries have suffered over time, as well as the deficiencies in some entries and meanings in early compilations (which have since been addressed), and the rigidity of some authors in accepting linguistic evidence, it has become essential for modern critics to verify all evidence before judging the correctness of linguistic usage.DOI: https://doi.org/10.54633/2333-025-058-013